ENGINEERING MODEL OF THE THERMAL REGIME IN DETACHED HOUSE - A. A. Varinov; N. D. Yakimov; Y. N. Erashova (Известия высших учебных заведений: Проблемы энергетики)
The article gives a mathematical description of heat transfer processes in all the heating elements, ranging from automatic gas water heater and ending on the residential areas. At the same time takes into account the major sources of heat, and possible ways of its dissipation. The result is a block diagram of a developed dynamic model of the heating system, which, together with the structure of the automatic control device can serve as a basic tool for the analysis and synthesis of the complex automated system.